Repress or Defect: Military Defections in Syria in 1982 and 2011 - Abulebada, Namat (AUC Knowledge Fountain, 2023)
This thesis investigates two events in modern Syrian history to understand military behavior under authoritarian regimes. It looks at and examines the behavior of the Syrian military in two cases: The Hama massacre of 1982, and the Syrian civil war from 2011 up until the end of 2012. The research studies how the same military, under similar conditions, could exhibit different behaviors when given orders of repression during anti-regime civil uprisings. The main research question tackled in the study is: why did large-scale military defections of out-group (Sunni) soldiers and officers occur in 2011 but not in 1982? Drawing on global literature on military loyalty and defections, as well as primary sources of the 2011 events, I focus on the nature of the two civil uprisings, and how they were perceived by the soldiers and officers of the Syrian military. The main results of investigation reflect on theories of ethnic stacking, military soldiers’ grievances, and the nature of the civil uprisings as enabling or inhibiting factors to military defection. The results of the thesis will be particularly useful to reflect on military loyalties in an increasingly militarized world.